The long arm provisions of capital gain tax: An analysis of the capital gains tax consequences on the indirect disposal of immovable property by non-residents in selected African Countries - Brooks, Miki (Department of Finance and Tax, 2017)
A non-resident who disposes of a direct interest in immovable property or an indirect interest in immovable property through the disposal of shares may be subject to capital gains tax in the country in which the immovable property is situated. Certain African countries were selected and the capital gains tax consequences on disposal of such property were determined by analysing the domestic tax legislation of the country in which the property is situated. In addition, the effect of any applicable double tax agreement ('DTA') to such disposals was considered. In certain countries - such as Angola and Nigeria - in terms of their domestic tax legislation, a non-resident will not be subject to capital gains tax in the respective country where the property is situated regardless of the value of the shares that is attributable to immovable property. In certain countries - such as Mozambique, Namibia, Tanzania and Zimbabwe - in terms of their domestic tax legislation, a non-resident may be subject to capital gains tax upon the disposal of an interest in immovable property in the respective country in which the immovable property is held regardless of the value of the shares that is attributable to immovable property, unless a DTA provides otherwise. In certain other countries - such as Botswana, Ghana, Lesotho and South Africa - in terms of their domestic tax legislation, a non-resident may be subject to capital gains tax upon the disposal of an interest in immovable property in the respective country in which the immovable property is held, however this will depend in general on the percentage of the value of shares that is attributable to immovable property, unless a DTA provides otherwise. Certain countries domestic tax legislation have specific provisions regulating how this percentage is determined. A DTA may provide relief to taxpayers who are subject to capital gains tax in both their resident country and the source country, on the disposal of an interest in immovable property held in the source country. In terms of domestic tax legislation, where the non-resident is liable to pay capital gains tax in the source country, the non-resident will in general have to comply with the withholding tax and filing obligations of that country where applicable.